The Impact of Falling Crude Oil Price on Financial Markets of Advanced East Asian Countries - Sultonov, Mirzosaid (Journal of Reviews on Global Economics, 2018)
We analysed the response of the financial markets of advanced East Asian countries to the significant decline in crude oil price which occurred in 2014. We used daily logarithmic returns of the representative exchange rates of national currencies and stock prices from 1 January, 2013 to 31 December, 2015. The empirical findings showed a significant change in both the dynamic correlation of exchange rates and stock prices and the causality relationship between the commodity, foreign exchange and stock markets during the period of declining crude oil price and instability. This paper highlights the response of the financial markets of advanced East Asian economies to a sharp decline in and instability of crude oil price, thereby contributing to the empirical literature and providing guidance for investment portfolio management.